2021
DOI: 10.3389/fonc.2021.683343
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: 18F-PSMA PET/CT May Improve the Clinical Management of Penile Metastases From Prostate Cancer

Abstract: Metastases from prostate cancer (PCa) to the penis are extremely rare, and few case reports exist in the literature. Because most patients usually present with multiple distant metastases at diagnosis, the prognosis is very poor. With the wide application of prostate-specific membrane antigen (PSMA) PET/CT, penile metastases may be detected at an early stage. Thus, questions regarding whether early diagnosis and precise treatment will equate to a survival advantage have recently been raised. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Penile metastasis of prostate cancer is rare ( 8 , 9 ), with only a few PSMA-targeted imaging presented in the literature ( 7 , 10 , 11 ), none of which underwent radical prostatectomy, and only ADT and external beam radiotherapy were performed in these cases. Castration resistance develops over time and the tumor can recur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penile metastasis of prostate cancer is rare ( 8 , 9 ), with only a few PSMA-targeted imaging presented in the literature ( 7 , 10 , 11 ), none of which underwent radical prostatectomy, and only ADT and external beam radiotherapy were performed in these cases. Castration resistance develops over time and the tumor can recur.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary penile tumors are rare and have a poor prognosis, with a mortality rate of 80% within 6 months, 28% of which is accounted for by prostate cancer ( 1 3 ). Previous literature has reported that penile metastasis occurs mainly secondary to primary prostate cancer without any medical treatment ( 4 , 5 ) or occurs during an androgen-deprivation therapy (ADT) without surgery ( 6 , 7 ). However, the present case represents a biochemical recurrence of prostate cancer in the penis during ADT after radical prostatectomy with a PSA of 0.072 ng/ml, which has not been reported in the literature so far.…”
Section: Introductionmentioning
confidence: 99%
“…Penile and penile bulb metastases from prostate cancer are historically considered rare 4 , 5 ; however, they are increasingly reported in the era of PSMA-based PET imaging. 6 , 7 , 8 , 9 , 10 , 11 Many of the reported cases included patients treated surgically who later experienced recurrence in the perineum or in patients treated only with ADT who later developed metastatic disease including a perineal site. 7 The patient described here was previously treated with prostate brachytherapy, raising the concern that the penile bulb disease was a result of tumor seeding along a biopsy tract or the brachytherapy needle track.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 8 , 9 , 10 , 11 Many of the reported cases included patients treated surgically who later experienced recurrence in the perineum or in patients treated only with ADT who later developed metastatic disease including a perineal site. 7 The patient described here was previously treated with prostate brachytherapy, raising the concern that the penile bulb disease was a result of tumor seeding along a biopsy tract or the brachytherapy needle track. Perineal seeding along the track of a needle biopsy was reported to occur in 0.17% to 1% of prostate biopsy cases, most often occurring in patients with locally advanced tumors, unlike this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection is important in management and preventing complications and thus may result in better treatment outcome. [ 4 7 8 9 ]…”
mentioning
confidence: 99%